2014
DOI: 10.1093/ageing/afu172
|View full text |Cite
|
Sign up to set email alerts
|

Safety of intravenous thrombolysis for ischaemic stroke in Asian octogenarians and nonagenarians

Abstract: octogenarians and nonagenarians receiving IVT have a similar safety outcome. Asian octogenarians and nonagenarians receiving IVT for ischaemic stroke are not at higher risk of symptomatic ICH and mortality than Western patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Emberson et al [18] reported: “Irrespective of age or stroke severity, and despite an increased risk of fatal intracranial hemorrhage during the first few days after treatment, alteplase significantly improves the overall odds of a good stroke outcome when delivered within 4.5 h of stroke onset, with earlier treatment associated with bigger proportional benefits”, a finding supported by Matsuo et al [20]. A series of smaller studies over the past 3 years [21,22,23,24,25] consistently found no difference in recanalization rate, in-hospital mortality, or incidence of intracranial hemorrhage in patients over 80 years when compared to younger cohorts, although some cautiously used a lower dose of rt-PA in the older group. Poorer outcomes were noted by Busl et al [26] after administration of rt-PA in elderly patients with pre-existing dementia, possibly due to underlying vascular pathology or amyloid angiopathy.…”
Section: Review Of the Evidencementioning
confidence: 95%
“…Emberson et al [18] reported: “Irrespective of age or stroke severity, and despite an increased risk of fatal intracranial hemorrhage during the first few days after treatment, alteplase significantly improves the overall odds of a good stroke outcome when delivered within 4.5 h of stroke onset, with earlier treatment associated with bigger proportional benefits”, a finding supported by Matsuo et al [20]. A series of smaller studies over the past 3 years [21,22,23,24,25] consistently found no difference in recanalization rate, in-hospital mortality, or incidence of intracranial hemorrhage in patients over 80 years when compared to younger cohorts, although some cautiously used a lower dose of rt-PA in the older group. Poorer outcomes were noted by Busl et al [26] after administration of rt-PA in elderly patients with pre-existing dementia, possibly due to underlying vascular pathology or amyloid angiopathy.…”
Section: Review Of the Evidencementioning
confidence: 95%
“…Whether statin use, in general, can reduce sICH risk in Asians, as it did regardless of lobar or non-lobar location (OR=0.83) in a large Danish registry study [ 71 ], remains to be seen. As for rtPA in AIS, the Taiwanese population was not at higher risk for symptomatic ICH (4.8%) [ 72 ], whereas an international study comparing outcomes in Asian and non-Asian populations concluded a higher risk of ICH and earlier deterioration in Asians relative to non-Asians getting rtPA (OR 1.51) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 The safety and efficacy of treatment are comparable to those in other Asian and Western countries. 10,12 An in-hospital case management program to improve the quality of stroke care according to clinical guidelines was implemented in CCH in 2008. 13 The CCH Stroke Center is the first Taiwanese primary stroke program certified by the Joint Commission International for clinical care, 14 and therefore our results might be of significance to other hospitals.…”
Section: Discussionmentioning
confidence: 99%